Combined (18) F-fluorocholine and (18) F-fluoride positron emission tomography/computed tomography imaging for staging of high-risk prostate cancer - Kjölhede, Henrik; Ahlgren, Göran; Almquist, Helen; Liedberg, Fredrik; Lyttkens, Kerstin; Ohlsson, Tomas G; Bratt, Ola (BJU international, 2012)
Study Type - Diagnosis (cohort) Level of Evidence 2a What's known on the subject? and What does the study add? Positron emission tomography/computed tomography (PET/CT) with choline and fluoride for the detection of metastases in patients with prostate cancer have each been evaluated, with mixed results. Choline PET/CT has been evaluated against pelvic lymphadenectomy, generally with a low sensitivity but a high specificity; however, the study populations have been heterogenous. Fluoride PET/CT has been evaluated against other imaging methods, such as bone scan, single photon emission CT and MRI, and has been shown to have high specificity as well as sensitivity for bone metastases, but there are no studies with biopsy verification. This is the first study that evaluates the clinical use of both choline and fluoride PET/CT on the same patients in a well-defined population of patients with high-risk prostate cancer. OBJECTIVE: • To investigate how often positron emission tomography/computed tomography (PET/CT)scans, with both (18) F-fluorocholine and (18) F-fluoride as markers, add clinically relevant information for patients with prostate cancer who have high-risk tumours and a normal or inconclusive planar bone scan. PATIENTS AND METHODS: • Patients with prostate cancer with prostate specific antigen (PSA) levels between 20 and 99 ng/mL and/or Gleason score 8-10 tumours, planned for treatment with curative intent based on routine staging with a negative or inconclusive bone scan, were further investigated with a (18) F-fluorocholine and a (18) F-fluoride PET/CT. • None of the patients received hormonal therapy before the staging procedures were completed. RESULTS: • For 50 of the 90 included patients (56%) one or both PET/CT scans indicated metastases. • (18) F-fluorocholine PET/CT indicated lymph node metastases and/or bone metastases in 35 patients (39%). • (18) F-fluoride PET/CT was suggestive for bone metastases in 37 patients (41%). • In 18 patients (20%) the PET/CT scans indicated widespread metastases, leading to a change in therapy intent from curative to non-curative. • Of the patients with positive scans, 74% had Gleason score 8-10 tumours. Of the patients with Gleason score 8-10 tumours, 64% had positive scans. CONCLUSIONS: • PET/CT scans with (18) F-fluorocholine and (18) F-fluoride commonly detect metastases in patients with high-risk prostate cancer and a negative or inconclusive bone scan. • For 20% of the patients the results of the PET/CT scans changed the treatment plan.